Characteristics of the Military Estate (Pazhilal) in the Avar Nutsaldom on the Basis of Medieval Written Sources and Oral Tradition - Shahban Khapizov; Magomed Sheykhmagomedov (Banber Arevelagitut'yan Instituti, 2025)
On the basis of the Daghestani Arabic-language sources of the 16th-17th centuries we establish the presence of a military estate in the Avar Nutsaldom known as Pazhilal. They lived at least from the IX century until the second half of the XIV century in the fortress Akaro, a few kilometers north of Khunzakh, the capital of the Avar Nutsaldom. The written sources emphasize that, unlike the rest of the population, they did not pay taxes. Moreover, according to other sources, they received payment for their military service and had a number of agricultural plots, which they rented out and received additional income that allowed them to concentrate exclusively on their occupation, without being distracted by agricultural and other work. Oral tradition, archaeological excavations, written sources of the 19th - early 20th centuries as well as archival material of the 19th century allows us to more thoroughly characterize the subject of our study.